Outcome Measures for Central Nervous System Evaluation in Myotonic Dystrophy Type 1 May Be Confounded by Deficits in Motor Function or Insight - Hamilton, Mark J.; McLean, John; Cumming, Sarah; Ballantyne, Bob; McGhie, Josephine; Jampana, Ravi; Longman, Cheryl; Evans, Jonathan J.; Monckton, Darren G.; Farrugia, Maria Elena (Frontiers in Neurology, 2018)
Background Central nervous system involvement in myotonic dystrophy type 1 (DM1) is associated with cognitive deficits, impaired social performance and excessive somnolence, which greatly impact quality of life. With the advent of clinical trials in DM1, there is a pressing need to identify outcome measures for quantification of central symptoms that are feasible and valid. In this context, we sought to evaluate neuropsychological and self-reported measures currently recommended by expert consensus, with particular reference to their specificity for central nervous system involvement in a moderate-sized DM1 cohort. Methods Forty-five adults with DM1 and 20 controls completed neuropsychology assessments and symptom questionnaires. Those without contraindication also underwent MRI brain, from which global grey matter volume and white matter lesion volume were quantified. CTG repeat was measured by small pool PCR, and was screened for the presence of variant repeat sequences. Results The neuropsychology test battery was well tolerated and detected impairment across various domains in the DM1 group versus controls. Large effect sizes in the Stroop and Trail Making tests were however attenuated by correction for basic speed, which could be influenced by dysarthria and upper limb weakness respectively. Low mood was strongly associated with increased self-reporting of central symptoms, including cognitive impairment. Conversely, self-reported cognitive impairment did not predict poorer performance in neuropsychology assessments, and there was a trend towards greater self-reporting of low mood and cognitive problems in those with milder white matter change on MRI. Global grey matter volume correlated with performance in several neuropsychology assessments in a multivariate model with age and sex, while white matter lesion volume was associated with executive dysfunction reported by a proxy. Screening for variant repeats was positive in three individuals, who reported mild muscle symptoms. Conclusions Identification of outcome measures with good specificity for brain involvement in DM1 is challenging, since complex cognitive assessments may be compromised by peripheral muscle weakness and self-reported questionnaires may be influenced by mood and insight. This highlights the need for further large, longitudinal studies to identify and validate objective measures, which may include imaging biomarkers and cognitive measures not influenced by motor speed.